FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA DI PROVINSI KALIMANTAN SELATAN - MURSIDAH MURSIDAH; ENY FAHRATY (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
Mursidah (2019). Factors that affect employment in the province of South Kalimantan. Supervisor : Dra. Eny Fahrati, MP.This study was conducted to (1) Find out  the simultaneous of economic growth, provincial minimum wages, and population growth on employmentin South Kalimantan Province.The study was conducted in the south Kalimantan Province. Data is processed by testing multiple linear regression analysis using SPSS 22.Based on the analysis, the results of the study prove simultaneously that there is a negativeinfluence of population growth and a positive relationship between economic growth and provincial minimum wages on employment in the province of South Kalimantan. Partially that the provincial minimum wage in the previous year had a very significant influence on employment in the South Kalimantan Province.Keywords:Employment, populationgrowth,employment and economic growth.